Implementation of the E-Worksheet ‘Our Oxygen (O₂) Friends’ to Enhance Elementary School Students’ Learning Motivation in the Era of Education 5.0 - Nurul Laili, Serly; Ayu Prameswari, Dinar; Anjarwati, Ani (Wahana : Tridarma Perguruan Tinggi, 2024)
This study aims to examine the implementation of the Electronic Student Worksheet (E-LKPD) “Our Oxygen (O₂) Friends” as a tool to enhance elementary students’ learning motivation in the context of Education 5.0. The research was motivated by the low learning motivation observed among students, particularly in the Natural Science (IPA) subject, which involves numerous abstract concepts requiring innovative, interactive, and contextual learning media. A quasi-experimental design with a One Group Pretest–Posttest approach was employed, involving 27 fifth-grade students at MI Muhammadiyah 1 Probolinggo. The research instrument consisted of a reflection sheet based on Uno’s learning motivation indicators, including persistence, interest, attention, enthusiasm, responsibility, and engagement. The findings revealed a substantial improvement in students’ learning motivation, with the mean score increasing from 64.0 to 83.2, representing a 29.9% gain. The most notable improvements were observed in the indicators of interest (33.9%) and enthusiasm (33.8%). These results indicate that the E-LKPD provides a more engaging and enjoyable learning experience while simultaneously fostering early ecological awareness. Consequently, the Our Oxygen (O₂) Friends E-LKPD can be considered an innovative and effective learning medium that aligns with the objectives of 21st-century education.